1981
DOI: 10.1099/00222615-14-4-483
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against antigens of Candida albicans in patients with fungaemia and bacteraemia, studied by ELISA, precipitation, passive haemagglutination and immunofluorescence techniques

Abstract: SUMMARY. Antibodies against commercially available antigens of Candida albicans were assayed in 54 sera from 24 patients with fungaemia and in 66 sera from 33 patients with bacteraemia. In patients with persistent fungaemia, antibody was found during the week after the fungus was first cultured from the blood, but peak titres did not usually occur until the end of the second week. A significant rise of titre in C. albicans infection was observed in 50% of paired sera tested by passive haemagglutination (PHA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

1983
1983
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
1
8
0
2
Order By: Relevance
“…The application of indirect ELISA methods to the detection of antibodies to somatic or metabolic antigens of C. albicans has been described [28,29]. These investigations demonstrated a good correlation between ELISA and other serological tests when similar antigens were used.…”
Section: Candidosismentioning
confidence: 96%
See 1 more Smart Citation
“…The application of indirect ELISA methods to the detection of antibodies to somatic or metabolic antigens of C. albicans has been described [28,29]. These investigations demonstrated a good correlation between ELISA and other serological tests when similar antigens were used.…”
Section: Candidosismentioning
confidence: 96%
“…Little attention has been given to the means of discrimination between negative and positive test results in ELISA tests for IgG antibodies to C. albicans. In several investigations the absorbance of test sera has been compared with that of a group of reference sera from normal individuals [28,29]. Richardson et al [49] found that inclusion of one C. albicans precipitin-test-positive and 10 precipitintest-negative reference sera selected at random as internal standards in each ELISA run enabled good discrimination to be achieved between other precipitintest-negative and -positive sera.…”
Section: Candidosismentioning
confidence: 99%
“…Bei 9 dieser Serumpaare betrifft die signifikante Titerbewegung die l g M-Antikörper bzw. (6,12). Die unterschiedliche Persistenz der IgG-und l g M-Antikörper erfordert jedoch für den frühzeitigen Nachweis eines Antikörperabfalles eine .selektive Bestimmung der IgM-Anti-· körper (6).…”
Section: Candida -Hämagglutinationstestunclassified
“…Er erfaßt gegen Polydie allein in der Lage wäre, Candida-Endomykosen mit saccharid-Antigene der Zellwand gerichtete Antikörper hinreichender Zuverlässigkeit zu diagnostizieren oder von überwiegend -wenn auch nicht ausschließlich -der mucocutanen Candida-Mykosen und verstärkter CandiImmunglobulinklasse M. Die empfindliche Technik des da-Kolonisation der Schleimhäute zu differenzieren (1-Enzymimmunoassays wird bislang nur in Speziallabora-3). Trotzdem ist die Verlaufskontrolle der Candida-Antitorien für Candida-Serologie eingesetzt (12)(13)(14)(15)(16). körper im Serum nicht wertlos, da bei mykosegefährdeten· .…”
Section: Introductionunclassified
“…Furthermore, serology based on a single serum sample is biased by the time of sampling during a given stage of the Candida infection, thus giving rise to false-negative results. This particular shortcoming of serology can be overcome by serial sampling, in which the increase or fall of an antibody titer is a more reliable reflection of the correct diagnosis (8,10,13). In this manner, we evaluated the levels of several antibodies and antigens in relation to the pathogenesis of candidiasis in immunocompromised patients.…”
mentioning
confidence: 99%